1 | ÷ | 2 | × | ( | x | − | 1 | ) | = | 2 | ÷ | 3 | × | ( | 1 | − | x | ) |
方程左边 = | 1 2 | ( | x | − | 1 | ) |
1 2 | ( | x | − | 1 | ) | = | 2 | ÷ | 3 | × | ( | 1 | − | x | ) |
方程左边 = | 1 2 | x | − | 1 2 | × | 1 |
= | 1 2 | x | − | 1 2 |
1 2 | x | − | 1 2 | = | 2 | ÷ | 3 | × | ( | 1 | − | x | ) |
方程右边 = | 2 3 | ( | 1 | − | x | ) |
1 2 | x | − | 1 2 | = | 2 3 | ( | 1 | − | x | ) |
方程右边 = | 2 3 | × | 1 | − | 2 3 | x |
= | 2 3 | − | 2 3 | x |
1 2 | x | − | 1 2 | = | 2 3 | − | 2 3 | x |
1 2 | x | + | 2 3 | x | = | 2 3 | + | 1 2 |
7 6 | x | = | 2 3 | + | 1 2 |
7 6 | x | = | 7 6 |
x | = | 7 6 | ÷ | 7 6 |
= | 7 6 | × | 6 7 |
= | 1 | × | 1 |
x | = | 1 |